The protective effects of baicalin for respiratory diseases: an update and future perspectives - Song, Siyu; Ding, Lu; Liu, Guangwen; Chen, Tian; Zhao, Meiru; Li, Xueyan; Li, Min; Qi, Hongyu; Chen, Jinjin; Wang, Ziyuan; Wang, Ying; Ma, Jing; et al. (Frontiers in Pharmacology, 2023)
Abstract: Background: Respiratory diseases are a common and frequent disease. Due to the high pathogenicity and side effects of respiratory diseases, the discovery of new strategies for drug treatment is a hot area of research. Scutellaria baicalensis Georgi (SBG) has been widely used as a medicinal herb in China for over 2000 years. Baicalin (BA) is a flavonoid active ingredient extracted from SBG, which plays a variety of pharmacological effects against respiratory diseases. However, there is no comprehensive review of the mechanism of the effects of BA in the treatment of respiratory diseases. This review aimed at summarizing the current pharmacokinetics of BA, the strategies to improve its oral availability, and its molecular mechanisms and therapeutical effects for the treatment of respiratory diseases. Method: This review reviewed databases such as PubMed, NCBI, and Web of Science from their inception to December 13, 2022, in which literature was related to “COVID-19”, “acute lung injury”, “pulmonary arterial hypertension”, “asthma”, “chronic obstructive pulmonary disease”, “pulmonary fibrosis”, “lung cancer”. Result: The pharmacokinetics of BA involves mainly gastrointestinal hydrolysis, the enteroglycoside cycle, multiple metabolic pathways, and excretion in bile. Co-administration of BA with other herbal extracts or drugs reflects altered in vivo profile and pharmacokinetics. Due to the poor bioavailability and solubility of BA, liposomes, polymer-lipid nanoparticles, solid nanocrystals, and nanoemulsion formulations of BA have been developed to improve bioavailability. BA exerts potent effects mainly by mediating upstream oxidative stress, inflammation, apoptosis, and immune response pathways. The main pathways it regulates are the NF-κB, PI3K/AKT, TGF-β/Smad, Narf2/HO-1, and ERK/GSK3β pathways. Conclusion: This review presents comprehensive information on BA about pharmacokinetics, strategies to improve bioavailability, and its therapeutic effects and potential pharmacological mechanisms in respiratory diseases. The available studies suggest that BA has great potential for the treatment of respiratory diseases and is worthy of further investigation and development.